2015
DOI: 10.1016/j.molp.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Allele of GS2 Enhances Grain Size and Grain Yield in Rice

Abstract: Grain size determines grain weight and affects grain quality. Several major quantitative trait loci (QTLs) regulating grain size have been cloned; however, our understanding of the underlying mechanism that regulates the size of rice grains remains fragmentary. Here, we report the cloning and characterization of a dominant QTL, grain size on chromosome 2 (GS2), which encodes Growth-Regulating Factor 4 (OsGRF4), a transcriptional regulator. GS2 localizes to the nucleus and may act as a transcription activator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
324
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(334 citation statements)
references
References 36 publications
6
324
0
4
Order By: Relevance
“…In contrast, KGW performance in hybrid rice is very stable, and the related QTLs function mainly in an additive manner, as shown in our study and by others (15,36). Thus, improved seed yield will benefit from pyramiding more QTLs from both parents, especially those that do not have a negative effect on other traits (56)(57)(58). Genetic analysis revealed that most QTLs detected in this study showed incomplete dominance and dominance effects, implying that dominance plays a leading role in driving yield heterosis and that it is possible to generate higher-yield hybrid rice by pyramiding more superior alleles.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, KGW performance in hybrid rice is very stable, and the related QTLs function mainly in an additive manner, as shown in our study and by others (15,36). Thus, improved seed yield will benefit from pyramiding more QTLs from both parents, especially those that do not have a negative effect on other traits (56)(57)(58). Genetic analysis revealed that most QTLs detected in this study showed incomplete dominance and dominance effects, implying that dominance plays a leading role in driving yield heterosis and that it is possible to generate higher-yield hybrid rice by pyramiding more superior alleles.…”
Section: Discussionsupporting
confidence: 52%
“…In rice, more than 400 QTLs that control grain shape traits have been detected and at least 20 genes have been isolated by map-based cloning strategies (Huang et al 2013;Zuo & Li 2014;Hu et al 2015;Liu et al 2015a, b;Wang et al 2015a, b). Compared with the results of previous studies, it can be deduced that RK4 should not be the same locus as the report by Tan et al (2000) detecting a QTL between the RFLP markers RG360 and C734a affecting grain width and length-width ratio, and it is not either as the report by Xing et al (2002) detecting a QTL between the RFLP markers R3166 and RG360 controlling grain weight.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several genes that regulate grain size by influencing cell expansion have been reported in rice. The major QTL for grain size ( GS2 ) encodes Growth-Regulating Factor 4 (OsGRF4) (Che et al, 2015; Duan et al, 2015; Hu et al, 2015). OsGRF4/GS2 physically interacts with transcriptional coactivators GRF-interacting Factors (GIFs) to regulate grain size by increasing both cell expansion and cell proliferation in spikelet hulls (Duan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%